Making Every Subject Count: A Case Study of Drug Development Path for Medication in a Pediatric Rare Disease. Issue 4 (22nd August 2016) - Bhattacharya, I; Manukyan, Z; Chan, P; Harnisch, L; Heatherington, A
Abstract : Approximately 50% of rare diseases are evident in children. Fatal disease prognosis and lack of treatments causes 30% of affected children to not live past their fifth birthday. This clear sense of urgency demands innovation and acceleration in drug development. A case study is discussed highlighting the need for data‐rich phase I study design, extensive use of modeling and simulation, use of diverse data sources, and input from collaborators to respond to this urgent call.